Peran Negara Terhadap Penampuangan Anak Terlantar Menurut Perspektif Hukum Keluarga Islam - Abdul Zaky Habibi; Al Ghany Rahmakadi; Fathurrahman An-Naufal; Maulana Kesuma; Muhammad Rizki Fazlim Yusran (Tabayyun : Journal Of Islamic Studies, 2024)
The lack of strong government will to care for abandoned children and the absence of solid governance institutions in the government system are the main reasons for the operationalization of government's failure to recognise the state's responsibility for neglected children. Aside from that, there are a number of challenges in defending children's rights in Indonesia, particularly those of neglected children: the application of law enforcement itself, which is contingent upon the qualifications of law enforcement officers, infrastructure and facilities that support them, and the complete ineffectiveness of government programmes because of the inadequate protection of children's rights. youngster. The potential of the Indonesian economy; the lack of public awareness, particularly among parents, of children's rights; the ignorance of relevant institutions and society Regarding the terms of the International Convention on the Rights of the Child; and the lack of coordination between associated authorities and social groups on an intergovernmental and intersocial level. sector-specific and global collaboration.